2017
DOI: 10.1111/all.13257
|View full text |Cite
|
Sign up to set email alerts
|

The potential of anti‐infectives and immunomodulators as therapies for asthma and asthma exacerbations

Abstract: Asthma is responsible for approximately 25,000 deaths annually in Europe despite available medicines that maintain asthma control and reduce asthma exacerbations.Better treatments are urgently needed for the control of chronic asthma and reduction in asthma exacerbations, the major cause of asthma mortality. Much research spanning >20 years shows a strong association between microorganisms including pathogens in asthma onset, severity and exacerbation, yet with the exception of antibiotics, few treatments are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 123 publications
(212 reference statements)
1
54
0
Order By: Relevance
“…These findings suggest that there are a number of therapeutic opportunities to reduce the frequency and severity of viral respiratory illnesses and hopefully secondary effects on the incidence and exacerbation of asthma (Fig 3). The search goes on for effective antivirals and vaccines for RV and RSV, and several candidates are currently in clinical trials (reviewed by Edwards et al 152 ). Antiviral approaches also include strategies to enhance resistance to multiple respiratory viruses through administration of interferons or other immunostimulatory molecules.…”
Section: Conclusion and Therapeutic Opportunitiesmentioning
confidence: 99%
“…These findings suggest that there are a number of therapeutic opportunities to reduce the frequency and severity of viral respiratory illnesses and hopefully secondary effects on the incidence and exacerbation of asthma (Fig 3). The search goes on for effective antivirals and vaccines for RV and RSV, and several candidates are currently in clinical trials (reviewed by Edwards et al 152 ). Antiviral approaches also include strategies to enhance resistance to multiple respiratory viruses through administration of interferons or other immunostimulatory molecules.…”
Section: Conclusion and Therapeutic Opportunitiesmentioning
confidence: 99%
“…59,60 Several new molecules have been identified for the treatment of RSV infection and are currently in (advanced) preclinical or clinical development. 72,73…”
Section: Treatment For Rsvmentioning
confidence: 99%
“…There are only a few agents targeting the inhibition of the attachment of RV to the cell or uncoating viral RNA, and their clinical applicability is continuously questioned due to adverse events (pleconaril, vapendavir) or drug resistance (amantadine, rimantadine). 72,73 Prednisolone: In two separate randomized trials, oral corticosteroid, prednisolone, has been shown to increase the time to the physician-confirmed relapse within the following year by 20%-30%…”
Section: Treatment For Rvmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute respiratory tract infections (ARIs) are triggered predominantly not only by RSV and RV, but also influenza virus, coronavirus and parainfluenza virus are significant risk factors for asthma development in children, depending on the load and timing of exposure. Although up to 50% of all children suffer from ARIassociated wheeze, it is yet unknown why some of them develop asthma, while others restore their healthy status [114]. While viral infections shift the immune response to the Th2 side, anti-viral response carried out by mediators of the Th1 axis is reduced [34,115].…”
Section: Infections and The Microbiomementioning
confidence: 99%